Analisis Perhitungan Harga Pokok Produksi dan Penentuan Harga Jual Produk (Studi Usaha Kerupuk Ikan Bunda Oca Sungai Lekop, Kecamatan Bintan Timur, Kabupaten Bintan) - Burhan Latif; Sri Ruwanti; Asmaul Husna (AKUNTANSI DEWANTARA, 2021)
This study aims to analyze and determine the cost of goods manufactured using the full costing method and the selling price using the cost plus pricing method in the Usaha Kerupuk Ikan Bunda Oca. Full costing is a method of determining production costs consisting of raw material costs, direct labor costs, variable factory overhead costs, and fixed factory overhead costs. Cost plus pricing is a method of determining the selling price of a product by accumulating total cost and desired profit. The method used in this research is descriptive quantitative. Data were collected by direct observation and interviews in the field so that the types of data used were primary data and secondary data obtained from literature reviews. The results show that the basic production costs per kilogram for original and otak-otak fish crackers are approximately Rp23.667,93 and Rp27.596,95 respectively. In addition, the total selling prices including 50% profit per kilogram were estimated to be Rp36.361,17 and Rp42.265,07 for original and otak-otak fish crackers respectively. Our study suggested that the calculation of cost production using full costing method and the selling price using the cost plus pricing method are more effective and accurate compared with conventional methods. This is because the calculation is carried out by considering many cost elements during the production process.Keyword: Cost of Production, Full Costing, Cost Plus Pricing.